(untitled) (Praxis Educativa, 2012)
The problem of sedentarism and obesity in Chile is being faced with official programs from the Health Ministry, which, in 1998 created the National Council to promote the program “Chile-Life”. Its aims, up to 2010, are associated with risk factors, specifically in nutrition, sedentarism, tobacco problems and psycho-social environmental factors. To put this plan into practice, schools and places of work had to prove their condition as “Health Promoters”. An advance report of this National Plan in February 2005 presents information about: number of tested schools; interventions of primary attention connected with nourishment topics; physical activity and tobacco; families in extreme poverty conditions. The emerging problem, then, is that any problem at country level, must be understood in its context because the reality of schools and the social contexts around them should determine suitable plans for the particular situation of each school. The implementation of the national plansrequires a certain infrastructure and resources to practise physical training that most schools don’t have; besides, vulnerable areas don’t have green spaces where to do these activities in a safe way.